PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM (KOPERASI MAHASISWA UNIVERSITAS AHMAD DAHLAN) - Pradana, Cipto; Putri, Aulia Diana; Sumaryanto, Sumaryanto (JUAN: Jurnal Pengabdian Nusantara, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in driving economic growth, especially at the local and rural levels. One of the main challenge in managing MSMEs in Indonesia is the low adoption of accounting practices that comply with standars, which affects the quality of the financial report procudec. This study aims to examine the application of accounting in the Ahmad Dahlan University Student Cooperative (Kopmart UAD) MSMEs, as well as to evaluate the effectiveness of the financial report preparead in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The method used in this study is descriptive qualititative with a case study approach. The reaserch result show that althought Kopmart UAD has conducted Financial recording, its implementation is still manual and not systemic. This result in less accurate financial repost and complicated the bussines evaluation process. Therefore, an increase in human resourch capacity and the development of a recording system that meets standards is necessary so that financial reports can support sustainbility and appropriate decision-making in bisiness management.